2014
DOI: 10.1007/s11999-013-3385-9
|View full text |Cite
|
Sign up to set email alerts
|

Does Intensity of Surveillance Affect Survival After Surgery for Sarcomas? Results of a Randomized Noninferiority Trial

Abstract: Background Whether current postoperative surveillance regimes result in improved overall survival (OS) of patients with extremity sarcomas is unknown. Questions/purposes We hypothesized that a less intensive followup protocol would not be inferior to the conventional followup protocol in terms of OS. We (1) assessed OS of patients to determine if less intensive followup regimens led to worsened survival and asked (2) whether chest radiograph followup group was inferior to CT scan followup group in detecting pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 23 publications
(44 reference statements)
1
84
1
2
Order By: Relevance
“…Prior work suggests that, if detected early, such disease may be more easily treatable and, in some cases, even curable with complete metastasectomy [1,2]. Some studies conclude that more aggressive pulmonary screening may facilitate earlier detection of lung metastases and improve survival for soft tissue sarcoma, particularly for higher risk patients [5,6]; others, however, either failed to confirm this advantage or demonstrated that less frequent scans are more appropriate for lower risk patients [13,17,20]. Although the optimal imaging frequency and modality to maximize survival remain unknown, it is generally agreed that patients with sarcoma require some form of surveillance that should be designed to maximize the number of recurrences detected per examination performed; therefore, understanding the frequency and timing of these events is necessary to determine optimal followup schedules.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work suggests that, if detected early, such disease may be more easily treatable and, in some cases, even curable with complete metastasectomy [1,2]. Some studies conclude that more aggressive pulmonary screening may facilitate earlier detection of lung metastases and improve survival for soft tissue sarcoma, particularly for higher risk patients [5,6]; others, however, either failed to confirm this advantage or demonstrated that less frequent scans are more appropriate for lower risk patients [13,17,20]. Although the optimal imaging frequency and modality to maximize survival remain unknown, it is generally agreed that patients with sarcoma require some form of surveillance that should be designed to maximize the number of recurrences detected per examination performed; therefore, understanding the frequency and timing of these events is necessary to determine optimal followup schedules.…”
Section: Discussionmentioning
confidence: 99%
“…Practices such as discharging patients treated for low-grade tumours at 5 years, when evidence suggests they recur late, require review. A recently reported trial comparing standard follow-up, with greater intensity follow-up and more imaging, failed to show any difference in outcome [79]. Furthermore, a recent retrospective study of follow-up for detection of local recurrence, demonstrated that most are detected clinically, casting doubt on the utility of routine surveillance MRI scanning [80].…”
Section: Prognosis and Follow-up For Primary Diseasementioning
confidence: 99%
“…In a prospective randomized study on nonmetastatic soft tissue and bone sarcoma of the extremities, which included 226 patients with secondary pulmonary metastases, chest X‐ray was not less effective than CT in detecting pulmonary metastases and was not associated with an inferior survival. In the same study, a 6‐monthly FU interval could not conclusively be demonstrated as being noninferior to a 3‐monthly interval regarding survival . In a study including 148 relapsed patients with histopathologically diverse bone sarcomas of the extremities, eight of 57 patients with asymptomatic pulmonary recurrence survived.…”
Section: Discussionmentioning
confidence: 92%